2010
DOI: 10.1080/00288233.2010.482964
|View full text |Cite
|
Sign up to set email alerts
|

Inter-paddock annual dry matter yield variability for dairy farms in the Waikato region of New Zealand

Abstract: The objective of this study was to characterise paddock-to-paddock annual dry matter (DM) yield variability dairy farms in the Waikato region of New Zealand, as a first step towards improving the amount of pasture grown and eaten by dairy cows. Individual paddock herbage yield was determined by calibrated visual assessment for two research farms and by rising plate meter from two commercial farms. Annualised pasture yield for individual paddocks across farms ranged from 9500 to 26100 kg DM/ha/year. Within farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Time delays of temporal models (Diaz-Solís et al, 2009;Diaz-Solis et al, 2003;Sala, 2001) and factors related to soil water availability (Bell et al, 2013;Chapman et al, 2013), may explain this lack of relation. The interaction between soil and environment (weather) within farms should be considered when predicting individual paddock pasture growth and when devising paddock-scale management of inputs and animals (Clark et al, 2010).…”
Section: Productive Resultsmentioning
confidence: 99%
“…Time delays of temporal models (Diaz-Solís et al, 2009;Diaz-Solis et al, 2003;Sala, 2001) and factors related to soil water availability (Bell et al, 2013;Chapman et al, 2013), may explain this lack of relation. The interaction between soil and environment (weather) within farms should be considered when predicting individual paddock pasture growth and when devising paddock-scale management of inputs and animals (Clark et al, 2010).…”
Section: Productive Resultsmentioning
confidence: 99%
“…(). Identifying poor performing paddocks, which typically yield 100% less than the top paddocks (Clark et al ., ), determining the cause of this poor performance and shifting these paddocks up the pasture performance curve by addressing the cause of poor performance will form the basis of increasing the amount of pasture herbage utilized on future dairy systems, both automatic and conventional.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing SR is usually associated with an increase in grazing severity, and many studies have attributed the increased productivity of higher SR systems to an improvement in pasture utilization (Hoden et al, 1991;Macdonald et al, 2008). In contrast, the effect of increasing SR and defoliation severity on pasture production has been extensively studied but inconsistently reported (Donaghy and Fulkerson, 1998;Macdonald et al, 2008;Lee et al, 2009), and the evaluation of such effects is often complicated by alternative grazing decision rules (Clark et al, 2010) and the difficulties of extending the results of shorter term component-based or cutting experiments to field conditions (Anderson and Briske, 1995). Indeed, previous studies have also indicated that although variation in defoliation and plant regrowth patterns creates variability in sward structure and nutritive value (Possingham and Houston, 1990;Adler et al, 2001), the effects of such practices are frequently accentuated by the farm system SR (Laca and Demment, 1991).…”
Section: Introductionmentioning
confidence: 99%